Optimalisasi Pemasaran Digital Terhadap Bubur Ayam Spesial Pak Beng - Rimadias, Santi; Changgasukha, Arya; Hilton, Johnatan; Gouwtama, Brian; Cherard, Federico; Donato, Alden; Ishadi, Muhammad; Vinco, Daniel (PT. Riset Press International, 2024)
UMKM are the dominating business sector in Indonesia, but the marketing carried out is still not optimal to market their business. The existence of social media can increase the potential to get public interest in getting to know UMKM. The community service team helped and assisted Bubur Ayam Spesial Keluarga Pak Beng for social media creation, including Instagram, Linktree, and Tiktok as an effort to increase public interest in Bubur Ayam Spesial Keluarga Pak Beng. The results of creating social media and its content increase public interest, as well as marketing to Bubur Ayam Pak Beng.